Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2011)
Starting a new journal is never easy and this also holds true for Studies in Second Language Learning and Teaching. The first question that should be posed when the idea is conceived is whether there is demand for such a journal in the community and the distinctive features that will make it distinguishable from or perhaps even superior to other publications already in existence. The second challenge is convincing eminent scholars to agree to become part of the project, which is a fundamental issue for any journal which aspires to achieve some degree of prominence. Yet another problem is finding authors that will be willing to submit their work to the journal, thus ensuring that there is no risk that sooner or later it may run out of papers to publish. These should be not only big names who have already established themselves in the field and whose contributions will induce others to write for the journal, but also less known scholars both from Poland and across the world, as in the end it is the latter who will be the main contributors to the journal. There is also the question of quality, which involves careful screening and selection of papers, which may not be easy when the number of submissions is not high. It is also related to finding reviewers who are recognized experts in particular areas, a task that is becoming more and more difficult in the light of the fact that such scientific enterprises have been mushrooming in recent years. Moreover, it is necessary to satisfy the requirements of the national authorities charged with the responsibility of ensuring high quality of academic research, which is in itself a major challenge because these requirements are in a constant state of flux. There are also all the doubts and uncertainties concerning the layout, the style sheet and also the cover, technicalities it might seem, but in reality things that might to some extent affect the reception of the publication. Last but not least, there is a need for sufficient funding and cutting through all the red tape before the journal can finally go into print.